“A part of my life”. A qualitative study about perceptions of female genital mutilation and experiences of healthcare among affected women residing in Sweden - Eshraghi, Bita; Marions, Lena; Berger, Cecilia; Berggren, Vanja (BMC women's health, 2024)
Background Female genital mutilation (FGM) is defined as all procedures involving partial or total removal of the external female genitalia, or other injuries to them for non-medical reasons. Due to migration, healthcare providers in high-income countries need to better understand the consequences of FGM. The aim of this study was to elucidate women’s experiences of FGM, with particular focus on perceived health consequences and experiences of healthcare received in Sweden. Methods A qualitative study was performed through face-to-face, semi-structured interviews with eight women who had experienced FGM in childhood, prior to immigration to Sweden. The transcribed narratives were analyzed using content analysis. Results Three main categories were identified : “Living with FGM”, “Living with lifelong health consequences” and “Encounters with healthcare providers”. The participants highlighted the motives behind FGM and their mothers’ ambivalence in the decision process. Although the majority of participants had undergone FGM type 3, the most severe type of FGM, the lifelong health consequences were diverse. Poor knowledge about FGM, insulting attitude, and lack of sensitive care were experienced when seeking healthcare in Sweden. Conclusions Our findings indicate that FGM is a complex matter causing a diversity in perceived health consequences in women affected. Increased knowledge and awareness about FGM among healthcare providers in Sweden is of utmost importance. Further, this subject needs to be addressed in the healthcare encounter in a professional way.